Roundabout way of profiling Earth's atmosphere. - Digregorio, B.E (IEEE spectrum)
The COSMIC (Constellation Observing Systems for Meteorology, Ionospheric and Climate) mission was initiated to take measurements of temperature and humidity in the atmosphere by means of a technique called radio occultation. A collaboration between the US and the Taiwanese National Space Organization, the mission involves the launching of six microsatellites aboard a single US Air Force Minotaur rocket. Each microsatellite is equipped with a radio receiver that will pick up signals from the US Global Positioning System. The GPS radio occultation technique used by the COSMIC system is expected to deliver precise measurements since the receivers measure changes in the phase and amplitude of radio signals transmitted by GPS satellites, and not changes in radiant energy. The COSMIC system is able to provide 2500 soundings, distributed uniformly around the globe per day.